A novel cost estimation model for the urban regeneration of a slum: the case of Kibera (Nairobi) - Nesticò, Antonio; Russo, Federica; Maselli, Gabriella; Vietri, Michele (Frontiers in Sustainable Cities, 2025)
Today, about one billion people worldwide reside in slums and informal settlements, which show extreme poverty and social inequality. Implementing well-structured strategies and programmes to make these settlements safer and more sustainable for residents is a challenge for governments. Therefore, it is crucial to define models to accurately predict the costs of intervention and assess the economic feasibility of slum upgrading actions. The aim of this paper is first to define possible intervention scenarios for the informal city and then to characterise an innovative model for the rapid estimation of related construction costs. The model, based on a synthetic-comparative evaluation procedure, allows estimating the urban regeneration costs of a slum according to the intervention scenario, which is differentiated into minimal, barely satisfactory, and fully satisfactory levels. This provides economic actors and policy makers with the essential financial terms to determine the resources to be allocated to support slums. The model is applied to the case study of Kibera (Nairobi), one of the most challenged slums in the world. The results provide a measure of the transformation costs per capita. These costs turn out to be insignificant compared to the expected economic and social benefits in the long run.